In vitro adhesion properties of Shiga toxin-producing Escherichia coli isolated from cattle, food, and humans - Pradel, Nathalie; Etienne-Mesmin, Lucie; Thévenot, Jonathan; Cordonnier, Charlotte; Blanquet-Diot, Stéphanie; Livrelli, Valérie (Frontiers in Microbiology, 2015)
Shiga-toxin producing Escherichia coli (STEC) are able to cause serious illnesses ranging from diarrhea to hemorrhagic colitis and hemolytic-uremic syndrome (HUS). These bacteria colonize the digestive tract of humans and produce Shiga-toxins, which are considered to be essential for virulence and are crucial in lethal infection. Colon colonization is supposed to be a determinant step in the development of the infection, but the virulence traits that mediate this step are unclear. We analysed the ability of 256 STEC strains belonging to seropathotype A (the most virulent O157:H7 serotype) to seropathotype E (not involved in human disease) to adhere to HEp-2, HCT-8 and T84 cell lines. The adhesion levels were globally low, but the highest levels were associated to O26:H11 and O103:H2 strains of seropathotype B (associated with outbreaks and HUS but less commonly than serotype O157:H7), possessing both the eae and toxB genes.